BERDUKA DALAM KONTEKS AL-QUR’AN DAN HADIST - MR, Marwah; Mutmainnah, Besse; Santalia, Indo; Pujirana, Andi Isni (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
Grief is a multifaceted emotional response to significant loss, such as the death of a loved one, deteriorating health, or the loss of life’s meaning. This study aims to explore the grieving process through an integrative approach that combines Islamic perspectives with contemporary psychological theories. Using a descriptive qualitative method and literature review, this research examines grief through the interpretation of Qur’anic verses, Hadiths of the Prophet Muhammad (PBUH), and grief models developed by theorists such as Kübler-Ross, Engel, and Rando. Findings indicate that Islamic teachings emphasize patience and surrender (tawakkul) as essential attitudes in facing adversity, while psychological approaches underscore the importance of acknowledging and progressing through emotional stages of grief. The integration of spiritual values with psychological frameworks offers a comprehensive foundation for supporting individuals in mourning. Furthermore, the study highlights the influence of personal factors, psychosocial conditions, and spiritual support in facilitating emotional healing and recovery.Keywords: Loss, Grief, Islamic Approach, Grief Psychology, Spiritual Resilience, Emotional Recovery